The Lichen Museum - Palmer, A. Laurie (Book collections on Project MUSE., 2023)
"The Lichen Museum explores how the physiological characteristics of lichens provide a valuable template for reimagining human relations in an age of ecological and social precarity. Using this tiny organism as an emblem through which to navigate environmental and social concerns, Palmer implores us to envision alternative ways of living based on interdependence rather than individualism and competition"--